An exploration of the factors affecting the impact of overtime on personal and job-related outcomes in the Chinese IT industry - Yu, Jiaoyang (2019)
Overtime has become a widespread phenomenon in the current information age that creates high speed working pace and fierce competition in the high technology global economy. The influences of overtime in the workplace on employees’ health (physical health and mental health) and life have been widely studied. However, the possible factors that may moderate the adverse impacts of overtime on employees have been less widely investigated and the preceding findings are not always consistent. Although research does indicate that rewards and worktime control (WTC) may reduce the negative influences of overtime on employees, there is also a paucity of research studying specific effects of their sub-dimensions on employees’ mental health and life. A greater understanding of these effects on overtime workers is important for the development of future, more effective interventions to prevent or reduce overtime’s negative influences.